The beginnings of Western science : - Lindberg, David C. (University of Chicago Press, 1992)
This landmark book represents the first attempt in two decades to survey the science of the ancient world, the first attempt in four decades to write a comprehensive history of medieval science, and the first attempt ever to present a full, unified account of both ancient and medieval science in a single volume. In The Beginnings of Western Science, David C. Lindberg provides a rich chronicle of the development of scientific ideas, practices, and institutions from the pre-Socratic Greek philosophers to the late-medieval scholastics.